Design of an Emergency Medical Initial Assessment Completeness Information System Using the Waterfall Method at X Bandung Hospital - Suvikarni Zalukhu; Yuyun Yunengsih; Falaah Abdussalaam (Greenation Publisher & Yayasan Global Research National, 2025)
Emergency services require rapid and accurate patient assessment, usually using systematic approaches such as ABCDE (Airway, Breathing, Circulation, Disability, Exposure) and AMPLE (Allergies, Medications, Past medical history, Last oral intake, Events leading to illness/injury). This research aims to design and implement a web-based information system to improve the completeness and accuracy of initial medical assessments in emergency departments, overcoming problems in manual documentation practices. The system is developed using the Waterfall method, with Flask (Python) for the backend, HTML/CSS/JavaScript for the user interface, and SQLite for database management. The implemented system features an easy-to-use interface with login modules, patient registration, digital assessment forms, real-time completeness validation, and PDF exports. The test confirms functional reliability, with successful results in data input, validation, and reporting (100% success rate). Web-based systems significantly improve the completeness, readability, and accessibility of emergency medical assessments. By integrating structured digital forms and automated validation, the system reduces documentation errors and improves workflow efficiency.